Has secondary science program become an elite urban education product in the former colonized nation? - Alam, Gazi Mahabubul; Parvin, Morsheda (SAGE Publications, 2024)
A distinct education has become a heretical right for urban elites despite educational equality is an official agenda. This has not only widened the gaps between urban and rural counterparts but also developed discriminations amongst different classes of student within the urban schools. To validate this tenet, the facilities offered by various schools were compared. Yet, whether a particular secondary education program has become an exclusive right essentially for urban elites to deprive others; is not widely explored—an investigation of this study. Educational background and some selective socioeconomic status (SES) of 925,617 students; completed their secondary school certificate from 3,315 schools were collected to make comparison through descriptive analysis of secondary data. Findings note that secondary science education has become a popular program amongst the urban elites. Subsequently, they also perform well in the public examination. Furthermore, discussions suggest that science being an international education demands both formal and informal higher budgets. Hence, a greater success of urban elites in secondary science provision helps them to succeed successively in procuring higher education and thereby in job-market. Thus, a policy intervention is required to ensure an effective implementation of educational equity concept. © The Author(s) 2024.